3(3y+-2x)+2(5x+-4y)=

Simple and best practice solution for 3(3y+-2x)+2(5x+-4y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3y+-2x)+2(5x+-4y)= equation:


Simplifying
3(3y + -2x) + 2(5x + -4y) = 0

Reorder the terms:
3(-2x + 3y) + 2(5x + -4y) = 0
(-2x * 3 + 3y * 3) + 2(5x + -4y) = 0
(-6x + 9y) + 2(5x + -4y) = 0
-6x + 9y + (5x * 2 + -4y * 2) = 0
-6x + 9y + (10x + -8y) = 0

Reorder the terms:
-6x + 10x + 9y + -8y = 0

Combine like terms: -6x + 10x = 4x
4x + 9y + -8y = 0

Combine like terms: 9y + -8y = 1y
4x + 1y = 0

Solving
4x + 1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
4x + 1y + -1y = 0 + -1y

Combine like terms: 1y + -1y = 0
4x + 0 = 0 + -1y
4x = 0 + -1y
Remove the zero:
4x = -1y

Divide each side by '4'.
x = -0.25y

Simplifying
x = -0.25y

See similar equations:

| 7x+19+14x-28=180 | | 9u-5=-41 | | 170=x+(x+1)+(x+2) | | 188=110-x | | 82=4r-16 | | 2+3i=4+5i | | -(16*t^2)+10*t+10=0 | | -2+4w=-22 | | -21=2w-5 | | 3y-2wheny=9 | | -0.4545454h+0.777777777777778=0.2222222222222222 | | -0.4545454+0.777777777777778=0.2222222222222222 | | -6=9-n | | 156=-4(1+8n) | | 16n=304 | | 16n=340 | | 2k^2+9k=-4 | | -50+25x+3x^2=0 | | 5y=-32x+2 | | 9(u-1)=3u-39 | | -2(3x+5)-5(x-4)=12 | | .5+16=39 | | 2n^2-17n+21= | | 6-1/4= | | 5c-3d=13 | | 24m+18m= | | (180-22x-3)=180 | | (x+3)+(x-8)+8=55 | | -12t+9=117 | | 3p-6=36 | | (3x-5)(x+10)=0 | | 6-(-3+1)= |

Equations solver categories